68Ga-FAPI-04 PET-CT for molecular assessment of fibroblast activation and risk evaluation in systemic sclerosis-associated interstitial lung disease: a single-centre, pilot study - Bergmann, Christina; Distler, Jörg; Treutlein, Christoph; Tascilar, Koray; Müller, Astrid; Atzinger, Armin; Matei, Alexandru-Emil; Knitza, Johannes; Györfi, Andrea-Hermina; Lück, Anja; Dees, Clara; Soare, Alina; et al. (The Lancet Rheumatology, 2021)
Background: Interstitial lung disease (ILD) is the most common cause of death in systemic sclerosis. To date, the progression of systemic sclerosis-associated ILD is judged by the accrual of lung damage on CT and pulmonary function tests. However, diagnostic tools to assess disease activity are not available. Here, we tested the hypothesis that quantification of fibroblast activation by PET-CT using a 68Ga-labelled selective inhibitor of prolyl endopeptidase FAP (68Ga-FAPI-04) would correlate with ILD activity and disease progression in patients with systemic sclerosis-associated ILD. Methods: Between Sept 10, 2018, and April 8, 2020, 21 patients with systemic sclerosis-associated ILD confirmed by high-resolution CT (HRCT) within 12 months of inclusion and with onset of systemic sclerosis-associated ILD within 5 years or signs of progressive ILD and 21 controls without ILD were consecutively enrolled. All participants underwent 68Ga-FAPI-04 PET-CT imaging and standard-of-care procedures, including HRCT and pulmonary function tests at baseline. Patients with systemic sclerosis-associated ILD were followed for 6 months with HRCT and pulmonary function tests. We compared baseline 68Ga-FAPI-04 PET-CT uptake with standard diagnostic tools and predictors of ILD progression. The association of 68Ga-FAPI-04 uptake with changes in forced vital capacity was analysed using mixed-effects models. Follow-up 68Ga-FAPI-04 PET-CT scans were obtained in a subset of patients treated with nintedanib (follow-up between 6–10 months) to assess change over time. Findings: 68Ga-FAPI-04 accumulated in fibrotic areas of the lungs in patients with systemic sclerosis-associated ILD compared with controls, with a median standardised uptake value (SUV) mean over the whole lung of 0·80 (IQR 0·60–2·10) in the systemic sclerosis-ILD group and 0·50 (0·40–0·50) in the control group (p<0·0001) and a mean whole lung maximal SUV of 4·40 (range 3·05–5·20) in the systemic sclerosis-ILD group compared with 0·70 (0·65–0·70) in the control group (p<0·0001). Whole-lung FAPI metabolic active volume (wlFAPI-MAV) and whole-lung total lesion FAPI (wlTL-FAPI) were not measurable in control participants, because no 68Ga-FAPI-04 uptake above background level was observed. In the systemic sclerosis-ILD group the median wlFAPI-MAV was 254·00 cm3 (IQR 163·40–442·30), and the median wlTL-FAPI was 183·60 cm3 (98·04–960·70). 68Ga-FAPI-04 uptake was higher in patients with extensive disease, with previous ILD progression, or high EUSTAR activity scores than in those with with limited disease, previously stable ILD, or low EUSTAR activity scores. Increased 68Ga-FAPI-04 uptake at baseline was associated with progression of ILD independently of extent of involvement on HRCT scan and the forced vital capacity at baseline. In consecutive 68Ga-FAPI-04 PET-CTs, changes in 68Ga-FAPI-04 uptake was concordant with the observed response to the fibroblast-targeting antifibrotic drug nintedanib. Interpretation: Our study presents the first in-human evidence that fibroblast activation correlates with fibrotic activity and disease progression in the lungs of patients with systemic sclerosis-associated ILD and that 68Ga-FAPI-04 PET-CT might improve risk assessment of systemic sclerosis-associated ILD. Funding: German Research Foundation, Erlangen Anschubs-und Nachwuchsfinanzierung, Interdisziplinäres Zentrum für Klinische Forschung Erlangen, Bundesministerium für Bildung und Forschung, Deutsche Stiftung Systemische Sklerose, Wilhelm-Sander-Foundation, Else-Kröner-Fresenius-Foundation, European Research Council, Ernst-Jung-Foundation, and Clinician Scientist Program Erlangen.
CRIS-Team Scopus Importer:2021-02-26

68GA-FAPI-04 PET/CT STUDY EXTENSION FOR THE ASSESSMENT OF FIBROBLAST ACTIVATION AND RISK EVALUATION IN SYSTEMIC SCLEROSIS-RELATED INTERSTITIAL LUNG DISEASE - Bergmann, Christina; Distler, Jörg; Treutlein, Christoph; Tascilar, Koray; Müller, Astrid; Atzinger, Armin; Matei, Alexandru-Emil; Knitza, Johannes; Gyorfi, A. H.; Lueck, A.; Dees, Clara; Soare, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Assessment of myocardial fibrosis in patients with systemic sclerosis using [Ga-68]Ga-FAPI-04-PET-CT - Treutlein, Christoph; Distler, Jörg; Tascilar, Koray; Chenguiti Fakhouri, Sara; Györfi, Andrea-Hermina; Atzinger, Armin; Matei, Alexandru-Emil; Dees, Clara; Büttner-Herold, Maike; Kuwert, Torsten; Prante, Olaf; Bäuerle, Tobias; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2022)
Purpose Myocardial fibrosis (MF) is a factor of poor prognosis in systemic sclerosis (SSc). Direct in-vivo visualization of fibroblast activation as early readout of MF has not been feasible to date. Here, we characterize (68)Gallium-labeled-Fibroblast-Activation-Inhibitor-04 ([Ga-68]Ga-FAPI-04)-PET-CT as a diagnostic tool in SSc-related MF.Methods In this proof-of-concept trial, six SSc patients with and eight without MF of the EUSTAR cohort Erlangen underwent [Ga-68]Ga-FAPI-04-PET-CT and cardiac MRI (cMRI) and clinical and serologic investigations just before baseline and during follow-up between January 2020 and December 2020. Myocardial biopsy was performed as clinically indicated.Results [Ga-68]Ga-FAPI-04 tracer uptake was increased in SSc-related MF with higher uptake in SSc patients with arrhythmias, elevated serum-NT-pro-BNP, and increased late gadolinium enhancement (LGE) in cMRI. Histologically, myocardial biopsies from cMRI- and [Ga-68]Ga-FAPI-04-positive regions confirmed the accumulation of FAP(+) fibroblasts surrounded by collagen deposits. We observed similar but not equal spatial distributions of [Ga-68]Ga-FAPI-04 uptake and quantitative cMRI-based techniques. Using sequential [Ga-68]Ga-FAPI-04-PET-CTs, we observed dynamic changes of [Ga-68]Ga-FAPI-04 uptake associated with changes in the activity of SSc-related MF, while cMRI parameters remained stable after regression of molecular activity and rather indicated tissue damage.Conclusions We present first in-human evidence that [Ga-68]Ga-FAPI-04 uptake visualizes fibroblast activation in SSc-related MF and may be a diagnostic option to monitor cardiac fibroblast activity in situ.
CRIS-Team WoS Importer:2023-02-10

ASSESSMENT OF SYSTEMIC SCLEROSIS RELATED MYOCARDIAL FIBROSIS BY 68GA-FAPI-04 PET/CT - Treutlein, Christoph; Schmidkonz, Christian; Tascilar, Koray; Chenguiti Fakhouri, Sara; Dees, Clara; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Bäuerle, Tobias; Kuwert, Torsten; Uder, Michael; Schett, Georg; Distler, Jörg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

BIOPHYSICAL PROPERTIES OF MONOCYTES INDICATE DISEASE ACTIVITY, SEVERITY OF FIBROTIC OR MICROVASCULAR MANIFESTATIONS AND THE RISK FOR PROGRESSION IN SYSTEMIC SCLEROSIS - Matei, Alexandru-Emil; Marketa, K.; Xu, L.; Györfi, Andrea-Hermina; Boxberger, E.; Soteriou, D.; Papava, Maria; Prater, Julia; Hong, Xuezhi; Kraeter, M.; Schett, Georg; Guck, J.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

CIRCULATING MONOCYTES HAVE DISTINCT PHYSICAL PROPERTIES THAT CORRELATE WITH DISEASE ACTIVITY AND SEVERITY AND PREDICT PROGRESSION IN SYSTEMIC SCLEROSIS - Matei, Alexandru-Emil; Kubankova, Marketa; Györfi, A.H.; Boxberger, E.; Soteriou, Despina; Papava, Maria; Muth, J.; Kräter, Martin; Schett, Georg; Distler, Jörg; Guck, Jochen (Annals of the Rheumatic Diseases, 2021)
CRIS-Team WoS Importer:2021-09-24

Dipeptidylpeptidase 4 as a Marker of Activated Fibroblasts and a Potential Target for the Treatment of Fibrosis in Systemic Sclerosis - Soare, Alina; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Dees, Clara; Rauber, Simon; Wohlfahrt, Thomas; Chen, Chih Wei; Ludolph, Ingo; Horch, Raymund E.; Bäuerle, Tobias; von Hörsten, Stephan; Mihai, Carina; et al. (Arthritis and Rheumatology, 2020)
Objective: Expression of dipeptidylpeptidase 4 (DPP-4) identifies a dermal fibroblast lineage involved in scarring during wound healing. The role of DDP-4 in tissue fibrosis is, however, unknown. The aim of the present study was to evaluate DPP-4 as a potential target for the treatment of fibrosis in patients with systemic sclerosis (SSc). Methods: Expression of DPP-4 in skin biopsy samples and dermal fibroblasts was analyzed by real-time polymerase chain reaction, immunofluorescence, and Western blot analyses. The activity of DPP-4 was modulated by overexpression, knockdown, and pharmacologic inhibition of DPP4 using sitagliptin and vildagliptin. The effects of DPP4 inhibition were analyzed in human dermal fibroblasts and in different mouse models of SSc (each n = 6). Results: The expression of DPP-4 and the number of DPP-4–positive fibroblasts were increased in the fibrotic skin of SSc patients, in a transforming growth factor β (TGFβ)–dependent manner. DPP-4–positive fibroblasts expressed higher levels of myofibroblast markers and collagen (each P < 0.001 versus healthy controls). Overexpression of DPP4 promoted fibroblast activation, whereas pharmacologic inhibition or genetic inactivation of DPP4 reduced the proliferation, migration, and expression of contractile proteins and release of collagen (each P < 0.001 versus control mice) by interfering with TGFβ-induced ERK signaling. DPP4-knockout mice were less sensitive to bleomycin-induced dermal and pulmonary fibrosis (P < 0.0001 versus wild-type controls). Treatment with DPP4 inhibitors promoted regression of fibrosis in mice that had received bleomycin challenge and mice with chronic graft-versus-host disease, and ameliorated fibrosis in TSK1 mice (each P < 0.001 versus untreated controls). These antifibrotic effects were associated with a reduction in inflammation. Conclusion: DPP-4 characterizes a population of activated fibroblasts and shows that DPP-4 regulates TGFβ-induced fibroblast activation in the fibrotic skin of SSc patients. Inhibition of DPP4 exerts potent antifibrotic effects when administered in well-tolerated doses. As DPP4 inhibitors are already in clinical use for diabetes, these results may have direct translational implications for the treatment of fibrosis in patients with SSc.
CRIS-Team Scopus Importer:2020-01-10

DIPEPTIDYL-PEPTIDASE-4 (DPP4) IS A POTENTIAL NEW MOLECULAR TARGET FOR TREATMENT OF FIBROSIS - Soare, A. M.; Gyoerfy, H.; Matei, Alexandru-Emil; Dees, Clara; Zhang, Yun; Wohlfahrt, T.; Chen, Chih-Wei; Ramming, A.; Schett, Georg; Distler, Jörg (2018)
EVALuna2:34995

Dipeptidyl-Peptidase-4 (DPP4) Promotes Fibroblast Activation and Is a Potential Molecular Target for Treatment of Fibrosis - Soare, Alina; Gyoerfy, Hermina; Matei, Alexandru-Emil; Dees, Clara; Chen, Chih-Wei; Ramming, Andreas; Schett, Georg; Distler, Jörg (2017)
EVALuna2:33443

DYNAMIC CHANGES IN O-GLCNACYLATION REGULATE OSTEOCLAST DIFFERENTIATION AND BONE LOSS IN ARTHRITIS - Chen, Chih-Wei; Li, Y. N.; Trinh, Minh Thuong; Honglin, Z.; Matei, Alexandru-Emil; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, C.; Liang, Ruifang; Huang, M. C.; Lin, N. Y.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Dynamic changes in O-GlcNAcylation regulate osteoclast differentiation and bone loss via nucleoporin 153 - Li, Yi-Nan; Chen, Chih-Wei; Trinh, Minh Thuong; Zhu, Honglin; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Kuwert, Frederic; Hubel, Philipp; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, Christoph; et al. (Bone Research, 2022)
Bone mass is maintained by the balance between osteoclast-induced bone resorption and osteoblast-triggered bone formation. In inflammatory arthritis such as rheumatoid arthritis (RA), however, increased osteoclast differentiation and activity skew this balance resulting in progressive bone loss. O-GlcNAcylation is a posttranslational modification with attachment of a single O-linked β-D-N-acetylglucosamine (O-GlcNAc) residue to serine or threonine residues of target proteins. Although O-GlcNAcylation is one of the most common protein modifications, its role in bone homeostasis has not been systematically investigated. We demonstrate that dynamic changes in O-GlcNAcylation are required for osteoclastogenesis. Increased O-GlcNAcylation promotes osteoclast differentiation during the early stages, whereas its downregulation is required for osteoclast maturation. At the molecular level, O-GlcNAcylation affects several pathways including oxidative phosphorylation and cell-cell fusion. TNFα fosters the dynamic regulation of O-GlcNAcylation to promote osteoclastogenesis in inflammatory arthritis. Targeted pharmaceutical or genetic inhibition of O-GlcNAc transferase (OGT) or O-GlcNAcase (OGA) arrests osteoclast differentiation during early stages of differentiation and during later maturation, respectively, and ameliorates bone loss in experimental arthritis. Knockdown of NUP153, an O-GlcNAcylation target, has similar effects as OGT inhibition and inhibits osteoclastogenesis. These findings highlight an important role of O-GlcNAcylation in osteoclastogenesis and may offer the potential to therapeutically interfere with pathologic bone resorption.
CRIS-Team Scopus Importer:2022-08-05

ENGRAILED 1 COORDINATES CYTOSKELETAL ORGANIZATION TO PROMOTE MYOFIBROBLAST DIFFERENTIATION AND FIBROTIC TISSUE REMODELING - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Rigau, Aleix; Hong, Xuezhi; Honglin, Z.; Luber, M.; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; Distler, O.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Engrailed 1 coordinates cytoskeletal reorganization to induce myofibroblast differentiation - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Liang, Chunguang; Rigau, Aleix; Hong, Xuezhi; Zhu, Honglin; Luber, Markus; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; et al. (Journal of Experimental Medicine, 2021)
Transforming growth factor-β (TGFβ) is a key mediator of fibroblast activation in fibrotic diseases, including systemic sclerosis. Here we show that Engrailed 1 (EN1) is reexpressed in multiple fibroblast subpopulations in the skin of SSc patients. We characterize EN1 as a molecular amplifier of TGFβ signaling in myofibroblast differentiation: TGFβ induces EN1 expression in a SMAD3-dependent manner, and in turn, EN1 mediates the profibrotic effects of TGFβ. RNA sequencing demonstrates that EN1 induces a profibrotic gene expression profile functionally related to cytoskeleton organization and ROCK activation. EN1 regulates gene expression by modulating the activity of SP1 and other SP transcription factors, as confirmed by ChIP-seq experiments for EN1 and SP1. Functional experiments confirm the coordinating role of EN1 on ROCK activity and the reorganization of cytoskeleton during myofibroblast differentiation, in both standard fibroblast culture systems and in vitro skin models. Consistently, mice with fibroblast-specific knockout of En1 demonstrate impaired fibroblast-to-myofibroblast transition and are partially protected from experimental skin fibrosis.
CRIS-Team Scopus Importer:2021-07-30

Fibroblast growth factor receptor 3 activates a network of profibrotic signaling pathways to promote fibrosis in systemic sclerosis - Chakraborty, Debomita; Zhu, Honglin; Juengel, Astrid; Summa, Lena; Li, Yi-Nan; Matei, Alexandru-Emil; Zhou, Xiang; Huang, Jingang; Thuong Trinh-Minh; Chen, Chih-Wei; Lafyatis, Robert; Dees, Clara; et al. (Science Translational Medicine, 2020)
Aberrant activation of fibroblasts with progressive deposition of extracellular matrix is a key feature of systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease. Here, we demonstrate that the profibrotic cytokine transforming growth factor. selectively up-regulates fibroblast growth factor receptor 3 (FGFR3) and its ligand FGF9 to promote fibroblast activation and tissue fibrosis, leading to a prominent FGFR3 signature in the SSc skin. Transcriptome profiling, in silico analysis and functional experiments revealed that FGFR3 induces multiple profibrotic pathways including endothelin, interleukin-4, and connective tissue growth factor signaling mediated by transcription factor CREB (cAMP response element-binding protein). Inhibition of FGFR3 signaling by fibroblast-specific knockout of FGFR3 or FGF9 or pharmacological inhibition of FGFR3 blocked fibroblast activation and attenuated experimental skin fibrosis in mice. These findings characterize FGFR3 as an upstream regulator of a network of profibrotic mediators in SSc and as a potential target for the treatment of fibrosis.
CRIS-Team WoS Importer:2020-10-16

FIBROBLAST GROWTH FACTOR RECEPTOR 3 REGULATES THE ACTIVITY OF PROFIBROTIC CYTOKINE AND GROWTH FACTOR PATHWAYS TO DRIVE FIBROBLAST ACTIVATION AND TISSUE FIBROSIS IN SYSTEMIC SCLEROSIS - Chakraborty, Debomita; Zhu, H.; Juengel, A.; Summa, L.; Li, Y. N.; Bergmann, C.; Matei, Alexandru-Emil; Trinh-Minh, T.; Chen, Chih-Wei; Dees, Clara; Ramming, Andreas; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Fibroblast Subpopulations in Systemic Sclerosis: Functional Implications of Individual Subpopulations and Correlations with Clinical Features - Zhu, Honglin; Luo, Hui; Skaug, Brian; Tabib, Tracy; Li, Yi; Tao, Yongguang; Matei, Alexandru-Emil; Lyons, Marka A.; Schett, Georg; Lafyatis, Robert; Assassi, Shervin; Distler, Jörg (Journal of Investigative Dermatology, 2024)
Fibroblasts constitute a heterogeneous population of cells. In this study, we integrated single-cell RNA-sequencing and bulk RNA-sequencing data as well as clinical information to study the role of individual fibroblast populations in systemic sclerosis (SSc). SSc skin demonstrated an increased abundance of COMP+, COL11A1+, MYOC+, CCL19+, SFRP4/SFRP2+, and PRSS23/SFRP2+ fibroblasts signatures and decreased proportions of CXCL12+ and PI16+ fibroblast signatures in the Prospective Registry of Early Systemic Sclerosis and Genetics versus Environment in Scleroderma Outcome Study cohorts. Numerical differences were confirmed by multicolor immunofluorescence for selected fibroblast populations. COMP+, COL11A1+, SFRP4/SFRP2+, PRSS23/SFRP2+, and PI16+ fibroblasts were similarly altered between normal wound healing and patients with SSc. The proportions of profibrotic COMP+, COL11A1+, SFRP4/SFRP2+, and PRSS23/SFRP2+ and proinflammatory CCL19+ fibroblast signatures were positively correlated with clinical and histopathological parameters of skin fibrosis, whereas signatures of CXCL12+ and PI16+ fibroblasts were inversely correlated. Incorporating the proportions of COMP+, COL11A1+, SFRP4/SFRP2+, and PRSS23/SFRP2+ fibroblast signatures into machine learning models improved the classification of patients with SSc into those with progressive versus stable skin fibrosis. In summary, the profound imbalance of fibroblast subpopulations in SSc may drive the progression of skin fibrosis. Specific targeting of disease-relevant fibroblast populations may offer opportunities for the treatment of SSc and other fibrotic diseases.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Dermal fibrosis; Disease outcomes; Fibroblasts; SSc; Subpopulations

Identification of a Distinct Monocyte-Driven Signature in Systemic Sclerosis Using Biophysical Phenotyping of Circulating Immune Cells - Matei, Alexandru-Emil; Kubankova, Marketa; Xu, Liyan; Györfi, Andrea-Hermina; Boxberger, Evgenia; Soteriou, Despina; Papava, Maria; Prater, Julia; Hong, Xuezhi; Bergmann, Christina; Kraeter, Martin; Schett, Georg; et al. (Arthritis and Rheumatology, 2023)
Objective Pathologically activated circulating immune cells, including monocytes, play major roles in systemic sclerosis (SSc). Their functional characterization can provide crucial information with direct clinical relevance. However, tools for the evaluation of pathologic immune cell activation and, in general, of clinical outcomes in SSc are scarce. Biophysical phenotyping (including characterization of cell mechanics and morphology) provides access to a novel, mostly unexplored layer of information regarding pathophysiologic immune cell activation. We hypothesized that the biophysical phenotyping of circulating immune cells, reflecting their pathologic activation, can be used as a clinical tool for the evaluation and risk stratification of patients with SSc.Methods We performed biophysical phenotyping of circulating immune cells by real-time fluorescence and deformability cytometry (RT-FDC) in 63 SSc patients, 59 rheumatoid arthritis (RA) patients, 28 antineutrophil cytoplasmic antibody-associated vasculitis (AAV) patients, and 22 age- and sex-matched healthy donors.Results We identified a specific signature of biophysical properties of circulating immune cells in SSc patients that was mainly driven by monocytes. Since it is absent in RA and AAV, this signature reflects an SSc-specific monocyte activation rather than general inflammation. The biophysical properties of monocytes indicate current disease activity, the extent of skin or lung fibrosis, and the severity of manifestations of microvascular damage, as well as the risk of disease progression in SSc patients.Conclusion Changes in the biophysical properties of circulating immune cells reflect their pathologic activation in SSc patients and are associated with clinical outcomes. As a high-throughput approach that requires minimal preparations, RT-FDC-based biophysical phenotyping of monocytes can serve as a tool for the evaluation and risk stratification of patients with SSc.
CRIS-Team WoS Importer:2023-04-14

NCOA3 AMPLIFIES PROFIBROTIC TRANSCRIPTIONAL PROGRAMS IN SYSTEMIC SCLEROSIS - Dees, Clara; Pötter, Sebastian; Fuchs, Maximilian; Bergmann, Christina; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Soare, A.; Ramming, Andreas; Ceppi, Paolo; Schett, Georg; Kunz, Meik; Distler, H. W. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Orphan Nuclear Receptor Ror alpha Is a Key Regulator of Tgf beta- and WNT-Signaling in Fibrotic Diseases - Kagwiria, Rosebeth; Liang, Ruifang; Matei, Alexandru-Emil; Sihler, Niclas; Chen, Chih-Wei; Burris, Thomas; Distler, Oliver; Schett, Georg; Distler, Jörg (2018)
EVALuna2:34962

Possible adaptations of vascularised human skin equivalents to include rare cell populations and study fibroblast heterogeneity. Response to: ‘In search for the ideal anatomical composition of vascularised human skin equivalents for systemic sclerosis translational research: should we recruit the telocytes?’ by Manetti and Matucci-Cerinic - Matei, Alexandru-Emil; Distler, Jörg (Annals of the Rheumatic Diseases, 2019)
CRIS-Team Scopus Importer:2019-10-29
Keywords: disease activity; systemic sclerosis; treatment

Protein kinases G are essential downstream mediators of the antifibrotic effects of sGC stimulators - Matei, Alexandru-Emil; Beyer, Christian; Gyoerfi, Andrea-Hermina; Soare, Alina; Chen, Chih-Wei; Dees, Clara; Bergmann, Christina; Friebe, Andreas; Hofmann, Franz; Distler, Oliver; Schett, Georg; Distler, Jörg; et al. (Annals of the Rheumatic Diseases, 2018)
Stimulators of soluble guanylate cyclase (sGC) are currently investigated in clinical trials for the treatment of fibrosis in systemic sclerosis (SSc). In this study, we aim to investigate the role of protein kinases G (PKG) as downstream mediators of sGC-cyclic guanosine monophosphate (cGMP) in SSc.Mice with combined knockout of PKG1 and 2 were challenged with bleomycin and treated with the sGC stimulator BAY 41-2272. Fibroblasts were treated with BAY 41-2272 and with the PKG inhibitor KT 5823.PKG1 and 2 are upregulated in SSc in a transforming growth factor-?1 (TGF?1)-dependent manner, as an attempt to compensate for the decreased signalling through the sGC-cGMP-PKG pathway. Inhibition or knockout of PKG1 and 2 abrogates the inhibitory effects of sGC stimulation on fibroblast activation in a SMAD-independent, but extracellular signal-regulated kinase (ERK)-dependent manner. In vivo, sGC stimulation fails to prevent bleomycin-induced fibrosis in PKG1 and 2 knockout mice.Our data provide evidence that PKGs are essential mediators of the antifibrotic effects of sGC stimulators through interfering with non-canonical TGF? signalling. TGF?1 promotes its profibrotic effects through inhibition of sGC-cGMP-PKG signalling, sGC stimulation exerts its antifibrotic effects by inhibition of TGF?1-induced ERK phosphorylation.
EVALuna2:13304

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

PU.1 INHIBITOR DB1976 CONTROLS FIBROBLAST POLARIZATION IN SYSTEMIC SCLEROSISAND LEADS TO REGRESSION OF FIBROSIS IN DIFFERENT MODELS OF ORGAN FIBROSIS - Wohlfahrt, Thomas; Rauber, Simon; Luber, Markus; Soare, Alina; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Karouzakis, Emmanuel; Kiener, Hans; Pachera, Elena; Dees, Clara; Kreuter, Alexander; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Rapid single-cell physical phenotyping of mechanically dissociated tissue biopsies - Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Lopez Posadas, Rocío; Pradhan, Rashmita; Thoma, Oana-Maria; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Waldner, Maximilian; Distler, Jörg; Scheuermann, Stefan; Langejuergen, Jens; et al. (Nature Biomedical Engineering, 2023)
A method for the sequential assessment of the physical phenotypes of suspended cells singularized from tissue biopsies by mechanical dissociation allows for rapid diagnoses.
CRIS-Team WoS Importer:2023-05-05

Targeting of canonical WNT signaling ameliorates experimental sclerodermatous chronic graft-versus-host disease - Zhang, Yun; Shen, Lichong; Dreißigacker, Katja; Zhu, Honglin; Trinh, Minh Thuong; Meng, Xianyi; Tran Manh, Cuong; Dees, Clara; Matei, Alexandru-Emil; Chen, Chih-Wei; Ditschkowski, Markus; Krauss, Stefan; et al. (Blood, 2021)
Chronic graft-versus-host disease (cGVHD) is a major life-threatening complication of allogeneic hematopoietic stem cell transplantation. The molecular mechanisms underlying cGVHD remain poorly understood, and targeted therapies for clinical use are not well established. Here, we examined the role of the canonical WNT pathway in sclerodermatous cGVHD (sclGVHD). WNT signaling was activated in human sclGVHD with increased nuclear accumulation of the transcription factor β-catenin and a WNT-biased gene expression signature in lesional skin. Treatment with the highly selective tankryase inhibitor G007-LK, the CK1α agonist pyrvinium, or the LRP6 inhibitor salinomycin abrogated the activation of WNT signaling and protected against experimental cGVHD, without a significant impact on graft-versus-leukemia effect (GVL). Treatment with G007-LK, pyrvinium, or salinomycin almost completely prevented the development of clinical and histological features in the B10.D2 (H-2d) → BALB/c (H-2d) and LP/J (H-2b) → C57BL/6 (H-2b) models of sclGVHD. Inhibition of canonical WNT signaling reduced the release of extracellular matrix from fibroblasts and reduced leukocyte influx, suggesting that WNT signaling stimulates fibrotic tissue remodeling by direct effects on fibroblasts and by indirect inflammation-dependent effects in sclGVHD. Our findings may have direct translational potential, because pyrvinium is in clinical use, and tankyrase inhibitors are in clinical trials for other indications.
CRIS-Team Scopus Importer:2021-05-28

Targeting TGF-beta signaling for the treatment of fibrosis - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Distler, Jörg (Matrix Biology, 2018)
Transforming growth factor-alpha (TGF-beta) is widely recognized as a core pathway of fibrosis. Inhibition of TGF-beta signaling may thus offer potential for antifibrotic therapies. Long-term inhibition of TGF-beta signaling at the level of its isoforms and receptors can be associated with unacceptable adverse effects. However, TGF-beta regulates a myriad of intracellular signaling cascades to transmit its profibrotic effects and several of those pathways offer potential for pharmacologic intervention. Moreover, the multiple interactions of TGF-beta with other profibrotic pathways also yielded candidates for therapeutic intervention. In this review, we discuss selected targets within the TGF-beta pathway with high translational potential. (C) 2018 Elsevier B.V. All rights reserved.
EVALuna2:213258

The tyrosine phosphatase SHP2 controls TGFβ-induced STAT3 signaling to regulate fibroblast activation and fibrosis - Zehender, Ariella; Huang, Jingang; Gyoerfi, Andrea-Hermina; Matei, Alexandru-Emil; Thuong Trinh-Minh; Xu, Xiaohan; Li, Yi-Nan; Chen, Chih-Wei; Lin, Jianping; Dees, Clara; Beyer, Christian; Gelse, Kolja; et al. (Nature Communications, 2018)
Uncontrolled activation of TGFβ signaling is a common denominator of fibrotic tissue remodeling. Here we characterize the tyrosine phosphatase SHP2 as a molecular checkpoint for TGFβ-induced JAK2/STAT3 signaling and as a potential target for the treatment of fibrosis. TGFβ stimulates the phosphatase activity of SHP2, although this effect is in part counterbalanced by inhibitory effects on SHP2 expression. Stimulation with TGFβ promotes recruitment of SHP2 to JAK2 in fibroblasts with subsequent dephosphorylation of JAK2 at Y570 and activation of STAT3. The effects of SHP2 on STAT3 activation translate into major regulatory effects of SHP2 on fibroblast activation and tissue fibrosis. Genetic or pharmacologic inactivation of SHP2 promotes accumulation of JAK2 phosphorylated at Y570, reduces JAK2/STAT3 signaling, inhibits TGFβ-induced fibroblast activation and ameliorates dermal and pulmonary fibrosis. Given the availability of potent SHP2 inhibitors, SHP2 might thus be a potential target for the treatment of fibrosis.
EVALuna2:34477

Vascularised human skin equivalents as a novel in vitro model of skin fibrosis and platform for testing of antifibrotic drugs - Matei, Alexandru-Emil; Chen, Chih-Wei; Kiesewetter, Lisa; Györfi, Andrea-Hermina; Li, Yi Nan; Trinh-Minh, Thuong; Xu, Xiaohan; Tran Manh, Cuong; Van Kuppevelt, Toin; Hansmann, Jan; Jüngel, Astrid; Schett, Georg; et al. (Annals of the Rheumatic Diseases, 2019)
Objectives: Fibrosis is a complex pathophysiological process involving interplay between multiple cell types. Experimental modelling of fibrosis is essential for the understanding of its pathogenesis and for testing of putative antifibrotic drugs. However, most current models employ either phylogenetically distant species or rely on human cells cultured in an artificial environment. Here we evaluated the potential of vascularised in vitro human skin equivalents as a novel model of skin fibrosis and a platform for the evaluation of antifibrotic drugs. Methods: Skin equivalents were assembled on a three-dimensional extracellular matrix by sequential seeding of endothelial cells, fibroblasts and keratinocytes. Fibrotic transformation on exposure to transforming growth factor-β (TGFβ) and response to treatment with nintedanib as an established antifibrotic agent were evaluated by quantitative polymerase chain reaction (qPCR), capillary Western immunoassay, immunostaining and histology. Results: Skin equivalents perfused at a physiological pressure formed a mature, polarised epidermis, a stratified dermis and a functional vessel system. Exposure of these models to TGFβ recapitulated key features of SSc skin with activation of TGFβ pathways, fibroblast to myofibroblast transition, increased release of collagen and excessive deposition of extracellular matrix. Treatment with the antifibrotic agent nintedanib ameliorated this fibrotic transformation. Conclusion: Our data provide evidence that vascularised skin equivalents can replicate key features of fibrotic skin and may serve as a platform for evaluation of antifibrotic drugs in a pathophysiologically relevant human setting.
CRIS-Team Scopus Importer:2019-10-01
Keywords: fibroblasts; systemic sclerosis; treatment

VASCULARIZED THREE-DIMENSIONAL MODELS OF HUMAN SKIN FIBROSIS - Matei, Alexandru-Emil; Chen, Chih-Wei; Kiesewetter, L.; Györfi, Andrea-Hermina; Li, Y. N.; Trinh-Minh, T.; Van Kuppevelt, T.; Hansmann, J.; Juengel, A.; Schett, Georg; Groeber-Becker, F.; Distler, Jörg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic